Multiple in vivo footprints are specific to the active allele of the X-linked human hypoxanthine phosphoribosyltransferase gene 5' region: implications for X chromosome inactivation. - Hornstra, I K (1992)
Dosage compensation of X-linked genes in male and female mammals is accomplished by random inactivation of one X chromosome in each female somatic cell. As a result, a transcriptionally active allele and a transcriptionally inactive allele of most X-linked genes reside within each female nucleus. To examine the mechanism responsible for maintaining this unique system of differential gene expression, we have analyzed the differential binding of regulatory proteins to the 5' region of the human hypoxanthine phosphoribosyltransferase (HPRT) gene on the active and inactive X chromosomes. Studies of DNA-protein interactions associated with the transcriptionally active and inactive HPRT alleles were carried out in intact cultured cells by in vivo footprinting by using ligation-mediated polymerase chain reaction and dimethyl sulfate. Analysis of the active allele demonstrates at least six footprinted regions, whereas no footprints were detected on the inactive allele. Of the footprints on the active allele, at least four occur over canonical GC boxes or Sp1 consensus binding sites, one is associated with a potential AP-2 binding site, and another is associated with a DNA sequence not previously reported to interact with a sequence-specific DNA-binding factor. While no footprints were observed for the HPRT gene on the inactive X chromosome, reactivation of the inactive allele with 5-azacytidine treatment restored the in vivo footprint pattern found on the active allele. Results of these experiments, in conjunction with recent studies on the X-linked human PGK-1 gene, bear implications for models of X chromosome inactivation.